The peculiarities of the attitude of chronic somotic patients towards their disease in the resort treatment process - Streikus, Z.; Trimonytė, A. (Psichologija, 1990)
The paper analyses the attitude of chronic somatic patients towards their disease in the resort treatment process and its interrelationship with personality variables. Seven psychodiagnostic techniques were used with 250 chronic somatic patients. The data obtained revealed: inadequate attitude towards disease during the entire treatment process; more external locus control; high anxiety level; neurotic personality development; problems in interpersonal relations. The paper suggests the necessity of holistic approach to disease prevention and patient rehabilitation.
Keywords: chronic somotic patients; attitude toward disease